Correlation between Post-COVID-19, Chemosensitive Function, Blood Group, and Oral Health-Related Quality of Life. (11th May 2022) - Alabsi, Rehab Abdulwahab M.; Sandeepa, N. C.; Misfer, Rema Tariq; Alraqdi, Majdah Mahmood; Hamdi, Mohammed Ibrahim M.
Abstract : Background/Purpose . Several studies reported chemosensitive dysfunction in the olfactory and gustatory domains following coronavirus disease 2019 (COVID-19). However, the long-term convalescence period of these sensory functions and associated factors remains unknown. Hence, this study explored the correlation between post-COVID-19 conditions, chemosensitive function, blood group, and oral health-related quality of life. Materials and Methods . A cross-sectional information on demographics, symptomatic disease status, ABO blood group, and oral health-related quality of life (OHRQoL) was collected among 100 patients who were earlier tested positive for COVID-19 reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and were now reporting to the College of Dentistry for routine treatment after recovery. Objective evaluation of olfactory and gustatory disturbances was elicited using the Connecticut Chemosensory Clinical Research Center (CCCRC) test and gustatory function testing. Furthermore, OHRQoL was assessed using Oral Health Impact Profile (OHIP-14). Results . More than half of the patients (62%) had some form of olfactory dysfunction/alteration, and 42% had poor CCCRC scores. About 14% reported ageusia, while 68% reported some form of taste alterations, and 55% reported poor OHRQoL. A statistically significant difference was reported between different ABO blood groups and subjective loss of smell (p < 0.05 ). The subjective loss of taste, CCCRC score, and dysgeusia were found to be independent of OHIP-14 (p > 0.05 ), but the taste intensity score was dependent on OHIP 14 (p < 0.05 ). Moreover, a majority (70.8% and 70.0%) with poor OHIP-14 scores had taste intensity scores of 3 and 4, respectively, while those with moderate (68.4% and 48.6%) OHIP-14 had scored 1 and 2, respectively. Conclusion . Olfactory and gustatory disturbances were found to be a long-term feature in post-COVID-19 patients. The blood group is a predisposing factor for persistent smell alterations in post-COVID-19 patients.